1976
DOI: 10.1021/i260060a007
|View full text |Cite
|
Sign up to set email alerts
|

Coke Formation during Thermal Cracking of n-Octane

Abstract: Greek Letters B = aeration factor r = r function 0 = dimensionless time = m(GhdLM) p = viscosity, eq 32, g/cm s u = kinematic viscosity, eq 33, cm2/s p = density, g/cm3 or lb/ft3 u = surface tension, eq 32, dyn/cm u2 = dimensionless variance ut2 = time based variance, s2 4 = froth density factor on the tray $?Id = froth density factor in downcomer Literature CitedThe coking phenomenon as a function of temperature space time and surface to volume ratio ( s h ) of the 304 stainless steel reactor was investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
0
2

Year Published

1981
1981
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 10 publications
5
28
0
2
Order By: Relevance
“…A literature survey showed that kinetic studies of coke formation have been hampered by an insufficient knowledge of the chemical pathways leading to coke and by a lack of reliable information concerning the reactivity of individual hydrocarbons: consequently, the models proposed for coke formation were mainly empirical [10][11][12][13].…”
Section: State Of the Artmentioning
confidence: 99%
“…A literature survey showed that kinetic studies of coke formation have been hampered by an insufficient knowledge of the chemical pathways leading to coke and by a lack of reliable information concerning the reactivity of individual hydrocarbons: consequently, the models proposed for coke formation were mainly empirical [10][11][12][13].…”
Section: State Of the Artmentioning
confidence: 99%
“…It has been suggested that the formation of aromatics, including benzene, results from reactions of acetylene and acetylenic species (Frenklach and Taki, 1983;Tanzana and Gardiner, 1980;Brockhorn et al, 1983). Virk et al (1972) have discussed a possible mechanism for coke formation from benzene, and the carbon formation from thermal cracking of hydrocarbons has also been reviewed by Froment (1981) and Shah et al (1976). Table I indicates that the formation of graphitic carbon oscillates with increasing temperature.…”
Section: Resultsmentioning
confidence: 99%
“…In each case the metal content of catalyst was 2.5-2.5 wt.% of iron and cobalt, respectively. The sources of metals were their acetate, acetyl-acetonate, and nitrate salts (Fe(CH 3 COO) 2 …”
Section: Catalyst Preparationmentioning
confidence: 99%
“…At an early stage the main research activity aimed to avoid their formation [1,2], then, more and more researchers became familiar with special and valuable carbon forms such as carbon fibers [3,4], useful accumulation of hydrogen-rich coke depositions [5] or even carbon nanotubes [6,7].…”
Section: Introductionmentioning
confidence: 99%